(untitled) (Fiep Bulletin - online, 2011)
This article is the result of a research that aimed, through orality of former basketball players in the city of Rio Grande/RS, to present a version of the history from the memories of these personalities, as well as pointing some conditions of possibilities which caused recognizing of these memories´ collectivity. A historical survey (1935-1975), in which we collected oral testimonies from players of the time, analyzed newspapers reports about the appearing of basketball in the city, competitions and historical characters involved with the sport was made. This period presented elements about the city being a pioneer of the sport in the state, the influence of the clubs in the sportive conformation, the winning of championships and the athletes´ notoriety, which allowed us to think about the importance of this work, together with the oral testimonies of former athletes. These data were very important for mapping the local sportive memory, which relates to the selectivity of the souvenirs and their tension with the historical facts presented by the official documents. This work used the Oral History theoretical and methodological principles, through which those interviewed describe facts that are unknown to the social memory, as well as show elements which tension the sportive spectacle. This way, we can say that the historical versions presented by each one of the interviewed set up a new framework to the "history" of Rio Grande´s basketball and, with this, allowed to understand better the orality and the sportive memory of this space.